Modern wireless communications - Haykin, Simon (Delhi; Pearson, 2011)
This book provides a self-motivating introduction to wireless communications; it presents topics in a manner consistent with their natural evolution, based on the principle of increasing spectral efficiency of the radio transmission. TOPICS: Wireless Systems begins with a discussion of FDMA systems and follows with the evolution through TDMA, CDMA, and SDMA techniques. Engineering principles required for each multiple access strategy are presented parallel to it. For electrical engineers and others involved in wireless communications.
Keywords: Engineering and Allied Operations; Electrical Engineering; Wireless communication